PERBEDAAN PENGETAHUAN MASYARAKAT SEBELUM DAN SESUDAH DI BERIKAN PENYULUHAN KESEHATAN TENTANG SENAM DIABETES MELLITUS DI RT/RW 04/01 KELURAHAN PARUNG SERAB CILEDUG KOTA TANGERANG - Beata Rivani; Elsavira Nuramaliah (Jurnal Kesehatan STIKes IMC Bintaro, 2019)
Menopause is a normal occurrence when the woman faced years of fertility decline, so that for some women Diabetes mellitus (DM) is a metabolic disorder disease which is chronic progressive hiperglikemi symptoms, accompanied by disturbance due to the secretion of insulin. Gymnastics diabetes is low aerobic gymnastics imact and rithmis movement of fun is not boring and can be followed by all age groups so as to attract enthusiasm. This type of research using quantitative descriptive. In the study sample used as many as 50 respondents and implemented in March 2019. The research of the variable levels of knowledge about gymnastics diabetes mellitus. Instrument in this study i.e., using a questionnaire. How researchers collect data that will be performed in the study was obtained from primary data and secondary data. Data analysis using univariate analysis, namely analyze against each of the variables from the results of each study to generate a frequency distribution and percentage of each variable. It is known that the results of the level of knowledge prior todo outreach gymnastics about diabetes mellitus stated that the majority of the level of knowledge on the category less i.e. as many as 37 respondents (74.0%), category enough sebanyak 13respondents(26.0%), and category both as much as 0 (0.0%) respondents. And sfter he does counseling obtained results the majority of communities in RT 04 in the category quite i.e. There are 30 respondents (60.0%), and in both there are 16 categories of respondents (32.0%), while in the category of less there are 4 respondents (8.0%).